Time-resolved fluorescence imaging for specific and quantitative immunodetection of human kallikrein 2 and prostate-specific antigen in prostatic tissue sections. - Siivola, P; Pettersson, K; Piironen, T; Lövgren, T; Lilja, H; Bjartell, A (2000)
OBJECTIVES: To design protocols for specific and quantitative immunohistochemical detection of human kallikrein 2 (hK2) using lanthanide chelate-labeled monoclonal antibodies (Mabs) and time-resolved fluorescence imaging. METHODS: Anti-prostate-specific antigen (PSA) Mabs were tested in microtiterplate assays for their ability to prevent PSA from cross-reacting with the anti-hK2 Mab 6H10. Europium-labeled 6H10 and terbium-labeled anti-PSA Mab 2E9, selected as the best blocker antibody, were used for dual-label immunodetection in routinely fixed benign (n = 7) and malignant (n = 5) prostate specimens. The amounts of IgG bound in tissue were calculated from drops containing known Mab concentrations. RESULTS: The use of anti-PSA Mab 2E9 for blocking diminished the cross-reaction from 5% to 0.3%. In the analyzed tissues, there was considerable variation in staining intensity for both proteins; PSA signals varied from 0.1 to 36.6 times that of hK2, with on average 10-fold more bound anti-PSA Mab than anti-hK2 Mab. In malignant tissue, the amounts of bound IgGs were lower and more variable than in benign tissue using both the anti-PSA Mab and the anti-hK2 Mab. The variation in signal intensities for PSA and hK2 correlated significantly in benign tissue (P >0.05), but not in benign hyperplastic and malignant specimens (P <0.05). CONCLUSIONS: Quantification of two lanthanide chelate-labeled antibodies bound in the same tissue section enabled comparison of PSA and hK2 content in individual cells. The average cellular content of hK2 relative to that of PSA was consistent with previous mRNA studies. The time-resolved fluorescence imaging-based quantification method has universal applicability in fixed tissue specimens.